Hippocampal connectivity dynamics and volumetric alterations predict cognitive status in migraine: A resting-state fMRI study - Seyda Cankaya; Behcet Ayyildiz; Dila Sayman; Umutcan Duran; Dogukan Ucak; Ramazan Karaca; Sevilay Ayyildiz; Ece Ozdemir Oktem; Hatice Lakadamyalı; Ceyhun Sayman; Ahmet Ozsimsek; Ali Yalçınkaya; et al. (NeuroImage)
The etiology of cognitive decline linked to migraine remains unclear, with a growing recurrence rate and potential increased dementia risk among sufferers. Cognitive dysfunction has recently gained attention as a significant problem among migraine sufferers that can be related to alterations in hippocampal function and structure. This study explores hippocampal subfield connectivity and volume changes in migraine patients.We recruited 90 individuals from Alanya University's Neurology Department, including 49 migraine patients and 41 controls, for functional and anatomical imaging. Using the CONN toolbox and FreeSurfer, we assessed functional connectivity and subfield volumes, respectively. Montreal Cognitive Assessment (MOCA) was used to assess cognition in the entire sample. As a result, migraine patients exhibited significantly lower MOCA scores compared to controls (p<.001). Also, we found significant differences in hippocampal subfields between migraine patients and control groups in terms of functional connectivity after adjusting for years of education; here we showed that the left CA3 showed higher connectivity with right MFG and right occipitolateral cortex. Furthermore, the connectivity of left fimbria with the left temporal lobe and hippocampus and the connectivity of the right hippocampal-tail with right insula, heschl's gyrus, and frontorbital cortex were lower in the migraineurs.Additionally, volumes of specific hippocampal subfields were significantly lower in the migraineurs (whole hippocampus p = 0.004, whole hippocampus head p = 0.003, right CA1 head p = 0.006, and right HATA p = 0.005) compared to controls. In conclusion, these findings indicate that migraine-associated cognitive impairment involves significant functional and structural brain changes, particularly in the hippocampus, which may heighten dementia risk. This pioneering study unveils critical hippocampal alterations linked to cognitive function in migraine sufferers, underscoring the potential for these changes to impact dementia development.